2015
DOI: 10.1007/s13365-015-0406-3
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated epigenetic aging in brain is associated with pre-mortem HIV-associated neurocognitive disorders

Abstract: Objective HIV infection leads to age-related conditions in relatively young persons. HIV-associated neurocognitive disorders (HAND) are considered among the most prevalent of these conditions. To study the mechanisms underlying this disorder, researchers need an accurate method for measuring biological aging. Here we apply a recently developed measure of biological aging, based on DNA methylation, to the study of biological aging in HIV+ brains. Design Retrospective analysis of tissue bank specimens and pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 78 publications
(85 reference statements)
5
66
0
Order By: Relevance
“…In addition, it seems well-established now that the latter seem to have an effect on the former. Although a large recent study suggested that HIV-1 infection may cause accentuated but not accelerated aging , many others have presented evidence of accelerated aging in chronically HIV-1-infected populations (Angelovich et al, 2015;Cassol et al, 2014;Chou et al, 2013;Gianesin et al, 2016;Horvath and Levine, 2015;Levine et al, 2016;Martin et al, 2013;Pathai et al, 2013Pathai et al, , 2014Pfefferbaum et al, 2014;Schrack et al, 2015), involving multiple immune system-and CNS-related functional deficits. This review highlighted the many commonalities between functional changes of microglia during HIV-1 infection and during aging, including cellular activation, arrested cell cycle progression and altered cellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it seems well-established now that the latter seem to have an effect on the former. Although a large recent study suggested that HIV-1 infection may cause accentuated but not accelerated aging , many others have presented evidence of accelerated aging in chronically HIV-1-infected populations (Angelovich et al, 2015;Cassol et al, 2014;Chou et al, 2013;Gianesin et al, 2016;Horvath and Levine, 2015;Levine et al, 2016;Martin et al, 2013;Pathai et al, 2013Pathai et al, , 2014Pfefferbaum et al, 2014;Schrack et al, 2015), involving multiple immune system-and CNS-related functional deficits. This review highlighted the many commonalities between functional changes of microglia during HIV-1 infection and during aging, including cellular activation, arrested cell cycle progression and altered cellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated DNAm age, primarily based on the Horvath algorithm, has been associated with a variety of diseases and health outcomes including cancer [51], HIV- [52] and Alzheimer’s-related [53] neurocognitive impairment, Parkinson’s disease [54] and shortened time to death [55, 56••, 57]. Five studies (Table 1) have evaluated the associations between trauma and/or PTSD and accelerated DNAm age using the Horvath and/or Hannum algorithms.…”
Section: Traumatic Stress and Accelerated Cellular Aging In The Epi/gmentioning
confidence: 99%
“…For instance, HIV and obesity are associated with increased liver fibrosis, and both accelerate the epigenetic clock more than would be expected compared with age-matched control specimens (11)(12)(13). Interestingly, obesity altered the epigenetic clock of the liver but not for any other tissue sites (11).…”
Section: Introductionmentioning
confidence: 96%